Knowledge and attitude of pregnant woman toward umbilical-cord-blood collection - Djuwantono, Tono (Indonesian Socety of Obstetrics and Gynecology, 2010)
Objective: Stem cell technology from umbilical cord blood (UCB) has developed fast as health services. UCB could be used in many kinds of disease. Private UCB bank has been operated in many places all over Indonesia. Thereâs a need for research to evaluate the knowledge and attitude of pregnant woman towards the act of collecting UCB. Method: This is a cross-sectional study base on question-naire given to 163 pregnant women in three private hospitals in the Bandung City from September - November 2009. The result was analyzed with Rank-spearman correlation and Kruskal-Wallis chisquare. Result: Most respondent were 20 - 29 years old pregnant women (54.6%), with educational level of strata-1 (S-1) (41.1%), with monthly income within 5 - 10 million rupiah (35.6%). This is the second pregnancy or more (42.9%), with gestational age less than 24 weeks (61.3%) and variative obstetric history (59.5%). The average level of knowledge was poor and attitude scale was uncertain (3.4). There is a significant correlation between age (p = 0.008%; CI 95%), level of education (p = 0.0001; CI 95%) and knowledge. There is a significant correlation between gestational age and attitude (p = 0.003; CI 95%). Respondentâs level of knowledge also has a significant correlation with attitude (Ïs = 0.421; p = 0.0001; CI 95%). Conclusion: This study described the respondentâs poor knowledge will influence their attitudes toward UCB collection, so it is necessary for disseminating more information on UCB as an effort to get better research result on UCB. [Indones J Obstet Gynecol 2010; 34-2: 97-100] Keywords: knowledge level, attitudes, collecting UCB, pregnant woman, the Bandung city